2021
DOI: 10.1080/17441692.2021.1980599
|View full text |Cite
|
Sign up to set email alerts
|

Chasing targets in a pandemic: The impact of COVID-19 on HIV outreach workers for MSM (men who have sex with men) in Jakarta, Indonesia

Abstract: The COVID-19 pandemic has had a significant impact on HIV services globally, including communitybased outreach programmes. This article draws on a qualitative study of HIV outreach workers for men who have sex with men (MSM) in Jakarta, Indonesia undertaken between July and September 2020. The research documented the impact of the COVID-19 pandemic on HIV outreach programmes for MSM based on interviews, focus group discussions and video diaries collected from outreach workers. As a result of the pandemic, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…12 Estimates from UNAIDS in 2023 revealed an alarmingly high HIV prevalence among key population groups at higher risk of HIV infection: 13.7% of people who inject drugs; 17.9% of men who have sex with men; 11.9% of transgender individuals; and 2.1% of sex workers. 11 Our study 6 and several other studies [13][14][15][16] have documented the impact of the COVID-19 pandemic on HIV programs and services in Indonesia. In our study, we noted that compared to the pre-pandemic period, individuals living with HIV who visited hospitals had a lower likelihood of starting anti-retroviral treatment (ART), staying in care, and adhering to ART during the pandemic. 17 These disruptions were due, among other things, to social distancing orders, lockdown, and healthcare workers being redeployed to work on COVID-19 testing, contact tracing, and surveillance activities.…”
mentioning
confidence: 62%
“…12 Estimates from UNAIDS in 2023 revealed an alarmingly high HIV prevalence among key population groups at higher risk of HIV infection: 13.7% of people who inject drugs; 17.9% of men who have sex with men; 11.9% of transgender individuals; and 2.1% of sex workers. 11 Our study 6 and several other studies [13][14][15][16] have documented the impact of the COVID-19 pandemic on HIV programs and services in Indonesia. In our study, we noted that compared to the pre-pandemic period, individuals living with HIV who visited hospitals had a lower likelihood of starting anti-retroviral treatment (ART), staying in care, and adhering to ART during the pandemic. 17 These disruptions were due, among other things, to social distancing orders, lockdown, and healthcare workers being redeployed to work on COVID-19 testing, contact tracing, and surveillance activities.…”
mentioning
confidence: 62%
“…Eleven studies in total reported providing HIV treatment and care during COVID-19 remotely through telehealth services such as telephone and videoconferencing. Five of the studies were from the United States of America (USA) [ 50 , 52 , 59 , 60 , 68 ] and one each from Zambia [ 63 ], Myanmar [ 62 ], Philippines [ 65 ], Indonesia [ 56 ], Tanzania [ 51 ], and Kenya [ 54 ]. These studies reported that providers completed the required paperwork, including conducting needs assessments electronically, either through e-mail or over the phone, to minimise in-person contact with their clients.…”
Section: Resultsmentioning
confidence: 99%
“…I draw on ethnographic fieldwork conducted since 2017 with Bergembira, primarily focused on the social relationships forged between outreach workers, their clients and healthcare workers in clinics and at hospitals. The research on which this article is based took place over approximately 4 months of participant observation during annual visits made to Indonesia between 2017 and 2019 as part of an ongoing collaborative ethnographic project with epidemiologists and physicians about peer-based outreach work and support groups for MSM (Hegarty, Nanwani, and Praptoraharjo 2020;Hegarty et al 2021). My anthropological engagement is thus oriented toward and takes place in collaboration with Indonesian researchers and activists invested in understanding the impact of health inequities on MSM and waria, an Indonesian transgender population (see Mallay et al 2021).…”
mentioning
confidence: 99%